(untitled) (Journal of actual problems of jurisprudence, 2018)
The article is devoted to the study of one of the subjective factors of law – making that affect the process of creating laws – lobbying. In the field of law-making, lobbying means the activity of certain social groups, which consists in influencing the adoption of a normative legal act in order to introduce its own interests into its content. Accordingly, the article reveals the concept and essence of subjective factors, the role of lobbying in the implementation of lawmaking, regulatory features, positive and negative aspects of lobbying. The purpose of the research is to determine the role of lobbying in the implementation of law-making and the rationale for its legal regulation. The scientific significance of the work lies in the fact that the article considers the forms of lobbying in the world law-making practice, identifies its positive and negative aspects, the need and the purpose of creating a unified system of legal regulation of lobbying. The practical significance of the work: the data reflected in the content of the article, as well as the conclusions can be used in the study of the Institute of parliamentarism, in the study of lobbying. Research methods are analysis, synthesis, comparison, statistical method, deduction. As a result of the study, the following conclusions are made: the lobby is an integral, especially important institution of lawmaking; to create an effective system of legal regulation of lobbying activities in Kazakhstan, it is necessary to determine its purpose, possible methods and forms of lobbying, taking into account foreign practice. The value of the study is that the article defines the influence of lobbying on the level of improving the efficiency of lawmaking, as well as its results. Practical significance of the results: the conclusions of the study can be taken as a basis for legal reforms carried out in the country Key words: lobbying, lawmaking, legal act, bill, legal regulation.